Holy war, holy peace : how religion can bring peace to the Middle East - Gopin, Marc (Oxford University Press, 2002)
The use of religion in inflaming the Palestinian/Israeli conflict represents one understanding of the Abrahamic traditions. Marc Goplin argues for a greater integration of the Middle East peace process with the region's religious groups.